Insights from the fructose‐derived product glucoselysine: Revisiting the polyol pathway in diabetic complications - Hiroko Yamaguchi; Ryoji Nagai (Journal of Diabetes Investigation)
ABSTRACT Advanced glycation end‐products (AGEs) have been extensively studied because of their close association with the onset and progression of diabetic complications. However, owing to their formation through diverse metabolic pathways, AGEs often reflect a wide range of pathological conditions rather than being specific to diabetic complications. Consequently, identifying an AGE that directly correlates only with diabetic complications remains a challenge. Chronic hyperglycemia not only saturates the glycolytic pathway but also upregulates the polyol pathway, leading to the excessive production of fructose, a highly reactive reducing sugar. Although it has long been understood that fructose‐derived AGEs contribute to diabetic complications, their chemical structures remain unidentified. Recent breakthroughs have revealed that glucoselysine (GL) is a primary fructose‐specific AGE. Unlike other AGEs, GL is exclusively formed from fructose and not from other reducing sugars, such as glucose or galactose. This specificity provides GL with a distinct advantage in that its production pathway can be traced, making it a reliable indicator of polyol pathway activity. Furthermore, emerging evidence suggests that GL levels correlate with the progression of diabetic complications, including both micro‐ and macrovascular complications, making it a promising biomarker. GL's potential extends beyond diagnostics, as it may serve as a therapeutic target for managing complications associated with prolonged hyperglycemia and enhanced of polyol pathway. This review focuses on the enhanced polyol pathway and the formation of GL and discusses its biochemical characteristics, clinical significance, and potential as a novel diagnostic marker and therapeutic target in diabetic care.